Valor diagnóstico de la escala de ansiedad y depresión de goldberg (EAD-G) en adultos cubanos (2016)
The study has as objective to obtain information for Cuban population about the predictive validity of the EADG for detecting people with psychopathologic dysfunctions, as well as to differentiate anxiety and depression. It worked with a non probabilistic sample, integrated by 548 subjects, of which 31.2% had a psychopathologic disease diagnosed by a psychiatrist or psychologist. For the analysis of the data, the methodology analysis of the curves ROC was used. It was found that the EADG showed an appropriate predictive value to identify people with psychopathologic dysfunctions, and difficulties to distinguish dysfunctions of anxiety and depression. Results support the evaluative strategy recommended by the authors of applying the screening items firstly.